PENERAPAN STRATEGI PEMBELAJARAN BERBASIS PROYEK DALAM MEMBUAT ALAT PERAGA IPA UNTUK MENINGKATKAN PRESTASI BELAJAR DAN KEAKTIFAN SISWA KELAS IV SDN CERMO 01 KARE MADIUN - Ani Sulistyarsi (Universitas PGRI Madiun, 2012)
Recent studies show that teaching practice is dominated by the use of classical method which results in reality that only 20% of the students actively take parts in the class activities. This research is attempted to develop students’ learning participation and achievement in Natural Science Subject under project-based learning strategy to make learning realia. The subjects of the research are the students of five graders of SDN Cermo 1 Kare. The data on the students’ achievement are drawn by means of test, and those of students’ learning activity are drawn by observation on their participation in discussion and realia making process. The analysis results in conclusions that: students’ achievement and activity develops. Threshold level can be achieved 37% higher. The students’ activity develops by 25%. The teacher’s activity develops by 22.91%. Students’ participation in making realia develops by 54%, students’ skill in fixing components develops by 55%. It can then be concluded that students’ learning participation and achievement in Natural Science Subject under project-based learning strategy to make learning realia can develop students’ learning achievement and activity.